Title of the article in English: The role of the Polish diaspora in Argentina in the preservation and transformation of the Polish national identity in a context of contemporary migration challenges (De Signos y Sentidos, 2025)
The article analyses the process of Polish migration to Argentina, focusing on the issue of preserving national identity in the context of integration with the local society. The history of migration is presented, from the first waves of immigration in the 19th century to contemporary challenges such as globalisation and changing forms of identity among the Polish diaspora. The role of institutions of Polish communities in Argentina, such as schools, churches and cultural organisations supporting the preservation of Polish heritage, was explored. This analysis shows how Poles in Argentina have successfully integrated into a multicultural society without losing their national identity.
Keywords: Polish diaspora; Polish community in Argentina; national identity; integration; cultural heritage; multiculturalism